When No One is Watching - Spinelli, Eileen; Johnson, David 1951 February 18- (Grand Rapids Mich. : Eerdmans Books for Young Readers, 2013)
When alone, a young girl enjoys dancing, singing, growling, and cheering but when anyone other than her best friend is watching, she is quiet and shy.
Accelerated Reader AR